Colin Sumner criminology through the looking-glass - Moxon, David (Palgrave pioneers in criminology, 2020)
This book explores the work of criminologist Colin Sumner. It re-presents his arguments and ideas on Marxism, ideology, censure, deviance, crime, underdevelopment, social control and the media; situating them in their wider social context. Moxon argues that Sumner should be restored within the criminology discipline as a pioneer who has produced works of great theoretical sophistication and insight. By systematically considering Sumner's entire output, the book shows how his thought involved a gradually deepening understanding of his core notion of ideological censure. His writing is also marked by a growing unease with the effects of late modern capitalism and the quagmire of censoriousness rife in the 21st century. This book makes clear that Sumner's work was remarkably prescient, and his ideas may help up to make sense of complicated times